Vario-scale data structures - Radan Šuba (A+BE: Architecture and the Built Environment)
The previous chapter presents state-of-the-art in map generalization at NMAs’ and continuous generalization. There is a noticeable technological shift towards continuous generalisation which supports interactive map use where users can zoom in, out and navigate more gradual way. Despite some research efforts there is no satisfactory solution yet. Therefore, this chapter introduces the truly smooth vario-scale structure for geographic information where a small step in the scale dimension leads to a small change in representation of geographic features that are represented on the map. With this approach there is no (or minimal) geometric data redundancy and there is no (temporal) delay any more between the availability of data sets at different map scales (as was and is the case with more traditional approaches of multi-scale representations). Moreover, continuous generalisation of real world features is based on the structure that can be used for presenting a smooth zoom action to the user.